2010
DOI: 10.26509/wp-201007
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Foreign-Exchange-Market Intervention during the Volcker-Greenspan Era

Michael D. Bordo,
Owen F. Humpage,
Anna Schwartz

Abstract: for their research assistance. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…We consider that the exchange rate movements in the fall of 1985 were mostly caused by exogenous exchange rate shocks for the following reasons. First, the Plaza Accord was a policy initiative in the dollar foreign exchange market which signaled a shift from a "minimalist approach to intervention" to an "activist approach" of the U.S. foreign exchange policy (Bordo et al 2015). Second, the success of these coordinated interventions was by no means obvious ex-ante.…”
Section: Narrative Sign Restrictionsmentioning
confidence: 99%
“…We consider that the exchange rate movements in the fall of 1985 were mostly caused by exogenous exchange rate shocks for the following reasons. First, the Plaza Accord was a policy initiative in the dollar foreign exchange market which signaled a shift from a "minimalist approach to intervention" to an "activist approach" of the U.S. foreign exchange policy (Bordo et al 2015). Second, the success of these coordinated interventions was by no means obvious ex-ante.…”
Section: Narrative Sign Restrictionsmentioning
confidence: 99%
“…Despite having separate legal authority for intervention, the Federal Reserve System found that it could not easily avoid participating in Treasury initiated operations. Under these circumstances, the FOMC feared, intervention must weaken confidence in the System's commitment to price stability, which at the time the committee was avidly attempting to strengthen (Broaddus and Goodfriend 1996, Goodfriend 2010, Bordo, Humpage, and Schwartz 2010b. While many other advanced countries followed suite, intervention operations never entirely ended.…”
Section: Introductionmentioning
confidence: 99%